(untitled) (Polis (Santiago), 2018)
Recently, some quantitative research works dedicated to the "third sector" have begun to circulate in Latin America, referring to the so-called "nonprofit sector" made up of private organizations that do not behave like traditional companies: they do not distribute profits , nor seek to obtain them. the emergence of this sector in the region has not been accompanied by an analysis of the real scale that it has. For this it is important to investigate, reached a stage of certain development, the organizational and action magnitudes that reach the entities of this sector. This article discusses some of the conceptualizations used to support recent research, proposing solid-based hypotheses.